Plant and Animal Protein Intakes Largely Explain the Nutritional Quality and Health Value of Diets Higher in Plants: A Path Analysis in French Adults - Perraud, Elie; Wang, Juhui; Salomé, Marion; Huneau, Jean-François; Lapidus, Nathanaël; Mariotti, François (Frontiers in Nutrition, 2022)
Diets higher in plants are associated with lower risks of chronic diseases. However, animal foods, which are rich in protein, are also rich in some important minerals and vitamins. We aim to decipher the relationship between plant-based diets (PBD) and different dimensions of diet quality by studying the importance of plant and animal proteins. Using data from a representative survey in France (INCA3, n = 1,125), we used path analyses as a mediation-like approach to decipher the importance of plant and animal proteins in the relationship between the plant-based diet index (PDI) and diet quality. We used three types of diet quality scores: nutrient security (SecDiet score), positive nutrient adequacy (AS from the PANDiet score), and long-term mortality risk of 4 diet-related diseases: coronary heart disease, stroke, type 2 diabetes, and colorectal cancer (HiDiet). The PDI was positively associated with the HiDiet but not significantly with the SecDiet or the AS. A mediation by plant protein was found for all diet quality scores (specific indirect effect: 0.04 SD for the SecDiet, 0.10 SD for the AS, and 0.10 SD for the HiDiet). Conversely, the association between PDI and the AS was negatively mediated by animal protein intake (specific indirect effect: -0.06 SD). In further detailed models, the association between PDI and diet quality was mainly positively mediated by protein foods from the fruit-vegetables-legumes group (0.01 SD for the SecDiet and 0.02 SD for the AS) and whole grains (0.02 SD for the AS). Our data suggest that the positive impact of plant-based diets on diet quality is largely driven by higher intakes of plant protein foods, especially from fruits-vegetables-legumes and whole grains. Conversely, lower animal protein intake tends to limit the positive impact of plant-based diets on overall positive nutrient adequacy. Protein sources appear critical to healthy plant-based diets.